Treatment with gemcitabine/cisplatin and durvalumab for advanced biliary tract cancer – real-world data from a multicenter German patient population - Florian Gerhardt; Christian Müller; Marino Venerito; Jack Chater; Raphael Mohr; Mara Egerer; Udo Lindig; Aaron Schindler; Sebastian Ebel; Janett Fischer; Maik Schwarz; Sonja Gehring; et al. (Journal of Cancer Research and Clinical Oncology)
Abstract Background Biliary tract cancers (BTCs) are a heterogeneous group of malignant cancers with an overall poor prognosis. For more than a decade, the standard palliative first-line therapy was cytotoxic chemotherapy with gemcitabine/cisplatin. The results of the TOPAZ-1 and KEYNOTE-966 trials have now introduced immune checkpoint inhibitors (ICIs) into first-line therapy. Methods Between July 2022 and March 2024, we retrospectively analyzed patients with advanced BTC who were treated with gemcitabine/cisplatin and durvalumab (GCD) at collaborating German university hospitals, tertiary hospitals, and outpatient oncology practices. Results A total of 90 patients were enrolled. The median overall survival (mOS) was 16 months, and the median progression-free survival (mPFS) was 5 months. The overall response rate (ORR) was 11.1%, and the disease control rate (DCR) was 41.1%. A perihilar primary tumor was significantly associated with better mPFS, while age group between 70 and 75 years and performance status of ECOG 2 at treatment initiation were significantly associated with poorer mOS. Adverse events (AEs) occurred in a total of 64% of patients. The most common grade 1 and grade 2 AEs included anemia (23%), thrombocytopenia (16%), neutropenia (10%), nausea (14%), and fatigue (16%). Grade 3 and grade 4 AEs included anemia (10%), thrombocytopenia (5%), and neutropenia (11%). Only one case of immune-mediated hypothyroidism (imAE) was documented. Conclusion Our real-world data support previously reported findings and further validate ICI based therapy as the standard of care for patients with advanced BTCs.